Language in time and space : a Festschrift for Werner Winter on the occasion of his 80th birthday - Winter, Werner, 1923-2010; Bauer, Brigitte L. M., 1961-; Pinault, Georges-Jean, 1955- (Trends in linguistics. Studies and monographs ;, 2003)
The honoree of this Festschrift has for many years now marked modern trends in diachronic and synchronic linguistics by his own publications and by stimulating those of numerous others. This collection of articles presents data-oriented studies that integrate modern and traditional approaches in the field, thus reflecting the honoree's contribution to contemporary linguistics. The articles relate to comparative data from (early) Indo-European languages and a variety of other languages and discuss the theoretical implications of phenomena such as linguistic universals, reconstruction, and langu.